2013
DOI: 10.1163/15685403-00003252
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Echinogammarus from Algerian fresh waters, Echinogammarus haraktis n. sp. (Peracarida, Amphipoda)

Abstract: Samplings in the area of Oum El Bouaghi yielded a new species, E. haraktis, belonging to the Echinogammarus simoni-group, in springs and wadis located on Mount EL Hamra in northeastern Algeria. The species is mainly characterised by the high number of long setae on the second antenna of both sexes, the lack of long setae on the basal segment of pereiopod 7 and on the exopodal segment of the uropod 3, and a much reduced second exopodal segment of uropod 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Samples were preserved in 96% alcohol on the field. All amphipods were identified at the species level using a stereomicroscope Olympus SZX16 (Olympus TM ) and adapted identification keys (Karaman and Pinkster, 1977;Pinkster, 1993), updated with new descriptions (Ayati et al, 2018;Fadil and Dakki, 2003, 2001Piscart et al, 2013). For some animals, microscopic slides were used to confirm the identification (see Ayati et al, 2018 for details on microscopic preparation).…”
Section: Data On Amphipodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were preserved in 96% alcohol on the field. All amphipods were identified at the species level using a stereomicroscope Olympus SZX16 (Olympus TM ) and adapted identification keys (Karaman and Pinkster, 1977;Pinkster, 1993), updated with new descriptions (Ayati et al, 2018;Fadil and Dakki, 2003, 2001Piscart et al, 2013). For some animals, microscopic slides were used to confirm the identification (see Ayati et al, 2018 for details on microscopic preparation).…”
Section: Data On Amphipodsmentioning
confidence: 99%
“…Echinogammarus Stebbing, 1899 E. afer Stock, 1974 13 E. annandalei (Monod, 1924) 8, 13 E. carthaginiensis Ayati, Dhaouadi, Mahmoudi, Piscart, 2018 1 E. dactyus G. Karaman, 1987 13 E. haraktis Piscart, Merzoug, Hafid, 201314 E. klaptoczi Schäferna, 1908 13 E. oujdae Dakki, 2003 5, 7 E. pungens (H. Milne Edwards, 1840) 13, 15 E. reductus Pinkster, 1993 13 E. simoni (Chevreux, 1894) 2, 8, 13, 16 E. tacapensis (Chevreux and Gauthier, 1924) 13 E. tunetanus Ayati, Dhaouadi, Mahmoudi, Piscart, 2018 1 E. valedictus Pinkster and Platvoet, 1990 13 Karaman, 1935) 7, 8, 10, 11, 12 G. marmouchensis Fadil and Dakki, 2006 6 G. maroccanus Fadil and Dakki, 2001 4 G. microps Pinkster and Goedmakers, 1975 11 G. riftalensis Fadil and Dakki, 2006 6 G. rouxi Pinkster and Goedmakers, 1975 7, 11 Chaetogammarus Martynov, 1924 C. saisensis Fadil et al, 20097 Rhipidogammarus Stock, 1971 R. rhipidiophorus (Catta, 1878) 3, 8, 9 sites (4.4%) harbored two species whereas all other sites are monospecific. From a diversity point of view, the genus Echinogammarus is the most diversified with 13 known species and likely three new species from Algeria were discovered in our study (ongoing description).…”
Section: Genus Species Referencesmentioning
confidence: 99%
“…Animals were collected with a hand net sampler and fixed in 96% ethanol in the field. The identification was based on the key of Echinogammarus [6], which has been updated with new descriptions of species from the genera Echinogammarus [5,7]. Amphipod slides were prepared using Faure's permament mounting medium after the maceration of material in lactic acid and coloration with pink lignin.…”
Section: Animal Sampling and Preparationmentioning
confidence: 99%
“…Most of the other species are restricted to a small territory around the type locality. However, recent works in Algeria [7] and in Tunisia [5] highlighted the presence of several species closely related to E. simoni. These works suggested that several species might have been misidentified as Echinogammarus simoni in the past.…”
Section: Introductionmentioning
confidence: 99%
“…In northwestern Algeria, hydrobiology programs are developing at a growing rate in the Tafna watershed (Belaidi et al 2004;Taleb et al 2008;Mahi 2007;Belaidi et al 2011Benhadji 2013and Mahi et al 2019. In recent years, underground fauna has been the subject of systematic studies to record the stygobian species of North-East Algeria (Merzoug et al 2010;Piscart et al 2013;Khaldoun et al 2016;Hadjab et al 2018 andAyati et al 2019), It is part of a global context of the stygobian fauna of Algeria and the stakes of the knowledge of the biodiversity of the underground ecosystems particularly the importance of invertebrates hosted by dug wells. So the objective of this study is to complete the results already obtained in the North-West / North-East of Algeria, by widening the study area.…”
Section: Introductionmentioning
confidence: 99%